A Hybrid Machine Learning Approach for Heart Disease Prediction with Ecg & Echo Analysis and Explainable Ai (Don Bosco Institute of Technology Delhi Journal of Research, 2026)
Cardiovascular diseases remain one of the leading causes of mortality worldwide, underscoring the urgent need for early detection and accessible diagnostic solutions. This paper presents a hybrid machine learning and deep learning framework that integrates electrocardiogram (ECG) and echocardiography (ECHO) analysis with explainable AI techniques to enhance heart disease prediction. The developed application incorporates five core features: individualized patient prediction, batch prediction via CSV input, model transparency through algorithmic explanations, ECG-based arrhythmia and myocardial irregularity detection, and an extended framework for ECHO evaluation, personalized recommendations, hospital locator integration, and automated report summarization. By combining multiple machine learning and deep learning algorithms with explainable AI methodologies, the system not only improves predictive accuracy but also ensures interpretability and user trust. Furthermore, the model highlights critical risk factors such as cholesterol and blood pressure, bridging the gap between predictive analytics and practical healthcare applications.